Implementasi Dan Implikasi Proyek “Madrosati Jannati” Dalam Meningkatkan Akhlakul Karimah Peserta Didik SD Negeri 24 Muntok Kabupaten Bangka Barat - Wanda Setiawan (Magister Pendidikan Agama Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Education is a teacher's guidance and coaching effort towards helping students understand, appreciate, and practice their religious teachings so that they become devoted and virtuous human beings. Forming religious experience in students can be done early by instilling a deep-rooted religious experience so that it can form akhlakul karimah as the mouth of the nation's national education goals. By making SD Negeri 24 Muntok West Bangka as a research location, this research seeks to focus on the questions: 1) How is the implementation of religious activities in shaping akhlakul karimah at SD Negeri 24 Muntok West Bangka?; and 2) How is the implementation of religious activities in shaping akhlakul karimah at SD Negeri 24 Muntok West Bangka? This research is descriptive qualitative research conducted at SD Negeri 24 Muntok West Bangka. The process of collecting data involves observation, documentation, and interviews with predetermined informants. The validity of the data is determined by triangulating sources and analyzing the data using interactive methods, starting with the collection, condensation, and presentation of the data and drawing conclusions or verifications. The results of this study indicate that first, the implementation of the formation of akhlakul karimah through religious activities at SD Negeri 24 Muntok West Bangka is in accordance with the school's vision and mission and is elaborated through the Madrosati Jannati project with daily, monthly, and annual activities. Daily activities consist of 3S1J, memorization of short chapters, congregational prayers (dhuha, dhuhur), literacy in reading and writing the Qur'an, and infaq. Annual activities are carried out through the implementation of PHBI activities consisting of Maulid Isra Mi'raj, flash pesantren, joint prayers, and syawalan. Second, the results of the implementation of religious activities at SD Negeri 24 Muntok West Bangka have proven to be effective in shaping students' akhlakul karimah, as evidenced by the behavior of students after participating in religious activities, where there is a better pattern of behavior change in accordance with the religious teachings that are guided and a strong awareness of acting according to religious teachings.